2015
DOI: 10.1103/physrevlett.114.093201
|View full text |Cite
|
Sign up to set email alerts
|

γ-Ray Spectra and Enhancement Factors for Positron Annihilation with Core Electrons

Abstract: Many-body theory is developed to calculate the γ-spectra for positron annihilation with valence and core electrons in the noble gas atoms. A proper inclusion of correlation effects and core annihilation provides for an accurate description of the measured spectra [Iwata et al., Phys. Rev. Lett. 79, 39 (1997)]. The theory enables us to calculate the enhancement factors γ nl , which describe the effect of electron-positron correlations for annihilation on individual electron orbitals nl. We find that the enhanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 31 publications
(54 reference statements)
1
59
1
Order By: Relevance
“…This can be done by using many-body theory, which allows one to study properties of small and large atoms (e.g., He and Xe) with a similar level of accuracy (see, e.g., Refs. [77,[84][85][86], where this has been implemented for positron-atom and positron-ion collisions and annihilation). Such treatment should overcome the deficiencies of the modelvan-der-Waals-potential approach and should enable one to calculate not only the scattering cross sections but also the Ps-atom pickoff annihilation rates.…”
Section: Discussionmentioning
confidence: 99%
“…This can be done by using many-body theory, which allows one to study properties of small and large atoms (e.g., He and Xe) with a similar level of accuracy (see, e.g., Refs. [77,[84][85][86], where this has been implemented for positron-atom and positron-ion collisions and annihilation). Such treatment should overcome the deficiencies of the modelvan-der-Waals-potential approach and should enable one to calculate not only the scattering cross sections but also the Ps-atom pickoff annihilation rates.…”
Section: Discussionmentioning
confidence: 99%
“…We also used the wave function of the bound state to calculate the annihilation rate, including important short-range correlation enhancement factors. 80,81 Although our description of the bound positron-molecule system is not ab initio, its simplicity enables clear physical insight into the problem. The model correlation potential contains at most one free parameter for each type of atom in the molecule: the cutoff radius (assuming that the values of the hybrid polarizabilities of the atoms are known).…”
Section: Discussionmentioning
confidence: 99%
“…Similar enhancement factors are used in calculations of positron annihilation in solids [44,45]. Recent many-body-theory calculations for atoms have shown that the enhancement factors are, to a good approximation, functions of the spin-orbital energy ε i [27,43]:…”
mentioning
confidence: 96%